Sex Bias in Classifying Borderline and Narcissistic Personality Disorder. Issue 10 (October 2015) - Braamhorst, Wouter; Lobbestael, Jill; Emons, Wilco H.M.; Arntz, Arnoud; Witteman, Cilia L.M.; Bekker, Marrie H.J.
<x xml:space="preserve">Abstract</x> Abstract This study investigated sex bias in the classification of borderline and narcissistic personality disorders. A sample of psychologists in training for a post-master degree (N = 180) read brief case histories (male or female version) and made DSM classification. To differentiate sex bias due to sex stereotyping or to base rate variation, we used different case histories, respectively: (1) non-ambiguous case histories with enough criteria of either borderline or narcissistic personality disorder to meet the threshold for classification, and (2) an ambiguous case with subthreshold features of both borderline and narcissistic personality disorder. Results showed significant differences due to sex of the patient in the ambiguous condition. Thus, when the diagnosis is not straightforward, as in the case of mixed subthreshold features, sex bias is present and is influenced by base-rate variation. These findings emphasize the need for caution in classifying personality disorders, especially borderline or narcissistic traits.